Hidden Effects of Seed Quality Breeding on Germination in Oilseed Rape (Brassica napus L.) - Hatzig, Sarah; Breuer, Frank; Nesi, Nathalie; Ducournau, Sylvie; Wagner, Marie-Helene; Leckband, Gunhild; Abbadi, Amine; Snowdon, Rod J. (Frontiers in Plant Science, 2018)
Intense selection for specific seed qualities in winter oilseed rape breeding has had an inadvertent negative influence on seed germination performance. In a panel of 215 diverse winter oilseed rape varieties spanning over 50 years of breeding progress in winter-type rapeseed, we found that low seed erucic acid content and reduced seed glucosinolate content were significantly related with prolonged germination time. Genome-wide association mapping revealed that this relationship is caused by linkage drag between important loci for seed quality and germination traits. One QTL for mean germination time on chromosome A09 co-localised with significant but minor QTL for both EA and GSL content. This suggested either potential pleiotropy or close linkage of minor factors influencing all three traits. Therefore a reduction in germination performance may be due to inadvertent co-selection of genetic variants associated with 00 seed quality that have a negative influence on germination. Our results suggest that marker-assisted selection of positive alleles for MGT within the modern quality pool can help breeders to maintain maximal germination capacity in new 00-quality oilseed rape cultivars.